Associations of age, body mass index and biochemical parameters with brain morphology in patients with anorexia nervosa. (30th October 2020) - Bang, Lasse; Tamnes, Christian Krog; Norbom, Linn Bonaventure; Thomassen, Rut Anne; Holm, Jill Solberg; Skotte, Laila Holgersen; Juliusson, Petur Benedikt; Mejlænder‐Evjensvold, Magnus; Rø, Øyvind
Abstract: OBJECTIVE: Accumulating evidence shows that patients with anorexia nervosa (AN) have globally reduced brain mass, including lower cortical volume and thickness, which largely normalizes following weight restoration. The underlying mechanisms for these processes are unknown, and how age and severity of emaciation are associated with brain morphology in AN is poorly understood. We investigated associations of age, body mass index (BMI) and biochemical parameters with brain morphology among patients in treatment. METHOD: We included 85 patients (94% female) aged 12–48 (mean = 23) years with quality controlled magnetic resonance imaging (MRI) data. T1‐weighted MRI images, clinical characteristics and biochemical parameters were retrospectively collected from hospital records. Brain morphology was measured using FreeSurfer, and associations investigated using regression models and correlations. RESULTS: Controlling for BMI, age showed significant associations with brain morphology generally concordant with typical brain developmental patterns. Controlling for age, BMI showed significant positive associations with cortical volume and thickness. There were no significant interaction effects between age and BMI. None of the biochemical parameters correlated significantly with brain morphology. CONCLUSION: Our findings suggest the presence of typical neurodevelopmental patterns in AN. Importantly, we showed that severity of emaciation is related to brain morphology reductions, underscoring the importance of weight restoration. Highlights: Age showed significant associations with brain morphology generally concordant with known typical brain developmental patterns Body mass index showed significant positive associations with cortical volume and thickness There were no significant interaction effects between age and body mass index on brain morphology, and none of the biochemical parameters correlated significantly with brain morphology